Nanomedicine: Treatment of Chronic Disease Using Gold Nano Thermo Robot (GNTR) Empowered With Nanotechnology Approaches - Zahid Hasan (21633029) (2024)
Nanotechnologists and medical researchers are working hard to develop new and innovative ways to use nanorobots as nanomedicine to improve healthcare outcomes and revolutionize the field of therapeutics. Nanotechnology has the potential to revolutionize healthcare by providing new ways of treating chronic diseases in the field of medicine. A “Gold Nano Thermo Robot” (GNTR) model has been proposed in this research article, which can be considered a nanomedicine that will deliver controlled thermal therapy to targeted malignant tissues without damaging healthy tissues. The proposed nanotherapeutic system, empowered with a nano sensor network, interbody body communication network, and Internet of nanomedical things, has been used to normalize and control hyperthermal waves in real-time that have been used to eliminate breast cancer cells using the “SEE and TREAT” technique. To generate hyperthermia, which has been irradiated by laser pulses to propose GNTR, a Coulomb explosion took place, and a huge amount of dispersed hyperthermia waves were produced. To convert the intensity of dispersed and irregular hyperthermia into a regulated and disciplined format, a Finite Difference Method has been used to develop a “Heat Control System.” A comparative analysis has been provided of the intricate relationship between the required radius of Gold Nano Thermo Robots and the volume depth of the tumor for penetration, with a keen focus on evaluating how different GNTR sizes fit or do not fit for the task of effectively treating tumors at various depths within cancer tumors. Furthermore, the effectiveness of treatment has multifaceted outcomes that have been acquired by the interplay between two critical factors, the temperature limit and therapy duration. By examining a comprehensive matrix of thermal therapy durations (ranging from 25 minutes to 60 minutes) alongside various temperature limits (ranging from 33°C to 60°C). The best fit and the best response therapy session have been verified with a temperature limit of 42 °C for 30 minutes, achieving near-complete tumor ablation with minimum harm to the healthy tissues. The complex physical effects on the Gold Nano Robots surfaces due to the Coulomb explosion procedure are also provided in the form of simulation analysis, and an explanation is given in nine panels. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3346958